Asuhan Keperawatan Klien yang Mengalami Bersihan Jalan Napas Tidak Efektif dengan Bronkopneumonia di RSUD Budhi Asih - Fredi Okta Yoga; Restu Iriani (Jurnal Persada Husada Indonesia, 2022)
Bronchopneumonia is a pulmonary inflammation, usually starting in the terminalis bronchioli. This study aims to carry out Nursing Care to clients who experience an Ineffective Breath Pathway with Bronchopneumonia. This research used descriptive qualitative design of case study approach with intervention. Participants in this study there are two people, namely client 1 and client 2. While the supporting participants are family and nurse room. Clients who were the subject of this study were clients with medical diagnoses of bronchopneumonia and ineffective airway nursing problems. The results of the assessment indicate the client's main complaint is cough with sputum and shortness of breath, based on the data enforced nursing diagnosis of ineffective airway clearance associated with increased sputum production.Planning covers the priority setting of nursing problems that is ineffective airway clearance is preferred because according to Maslow's theory of basic human needs, physiological needs are the most important needs are met. The objectives and criteria of the results are determined on the basis of SMART (specific, measurable, achievable, realistic, and time bond).The main nursing actions given to clients are chest physiotherapy or clapping. The result of evaluation data of nursing problem of airway clearance is not effective, on client 1 not resolved while in client 2 is resolved proved with normal breathing frequency data and no additional breath sound. The conclusion of this study is that if the nursing action of chest or chest physiotherapy is done well and effectively can alleviate and reduce the increase of sputum production on clients who experience ineffective airway cleansing with bronchopneumonia.